Analysing Educational Support Systems for Life Sciences Teachers in Integrating Environmental Education - Munasi, Khathutshelo Ronald (CV Sinergi Ilmu dan Publikasi, 2025)
Increasing environmental literacy and promoting sustainable development rely on the integration of Environmental Education (EE) into the Life Sciences curriculum. This study examines the support mechanisms available to Life Sciences teachers in the Vhembe District of South Africa, focusing on policy documents, instructional materials, and subject advisors. Data was collected through document analysis and semi-structured interviews with Life Sciences teachers and a subject advisor, employing a qualitative, phenomenological case study design. Based on Bronfenbrenner's Ecological Systems Theory, the results show that materials like textbooks and the Curriculum and Assessment Policy Statement (CAPS) only give basic advice and don't show how to effectively include EE in the curriculum. Subject advisors, while potentially valuable, face systemic constraints, emphasizing general curriculum objectives over specialized EE support. The study underscores the need for enhanced professional development, targeted resources, and better alignment between policy and classroom practices to support effective EE integration.